Rural Community Development: Need For Appropriate Technological Interventions: Harnessing Technological Solutions for Sustainable Rural Development (Journal of Advances and Scholarly Researches in Allied Education, 2016)
In India, villages have vast natural resources and these resources arefully utilized to boost the economic status of the villagers. A holisticapproach on each village is needed than random implementation and topographicalpresence. Hence, it is essential that NGO's, educational institutions shouldadopt villages within operating vicinity and implement projects to alleviaterural poverty. Along with sustainable programmes and projects in alleviation ofpoverty technological interventions play a crucial role? NGO's  can play a lead role in mapping the resourcesand tying  the people, resources, needsand markets with appropriate specialists and to bring out a transformation inthe geographical area. This requires a collaborative approach betweeneducational institutions, technology developers, disseminators, marketingagencies, funding agencies, competency of local people, line departments ofstate and union government etc. NGOs have to involve themselvesenthusiastically in such kinds of social development exercises and disseminateappropriate technology interventions for rural community development. In this direction the students of social work department used to workwith rural communities during their rural field work and rural camps. Theyidentify the problems in rural areas and also identify the resources availableand educate the community people about programmes, ways and means to get theprogrammes. Further the social work students conduct many awareness programmes aboutlatest technology intervention available and how to use them for sustainabledevelopment and for environmental protection.